An Oxy‐Anion Accelerated [1, 5]‐o‐Quinone Methide Shift During the Nucleophilic Epoxidation of Salicylfulvene. Issue 3 (3rd January 2020) - Yang, Mingwei; Basada, John; Gronert, Scott; Erden, Ihsan
Abstract : A new facet of nucleophilic fulvene epoxidations has been uncovered. 6‐Arylfulvenes containing an ortho or para hydroxyl group react with basic hydrogen peroxide in an unusual manner; the epoxidation of the fulvene exocyclic double bond is followed by a phenoxide ion‐initiated epoxide ring opening to form an o ‐quinone methide ( o ‐QM) intermediate. The resulting cyclopentadienolate undergoes an unusual oxy‐anion accelerated [1, 5]‐sigmatropic o‐QM shift . Computational studies reveal that the activation energy for the [1, 5]‐QM‐shift in the cyclopentadienolate intermediate is quite low, signifying the acceleration caused by the oxy‐anion group. Placement of a second hydroxyl group in the 6‐aryl ring at C5 epoxidation via electron donation to the o ‐QM carbon; instead, an intramolecular oxa‐6‐π‐electrocyclization of the o ‐QM intermediate onto the cyclopentadiene is observed. Abstract : Nucleophilic epoxidation of o ‐ or p ‐hydroxy substituted fulvenes proceed with epoxide ring opening giving o ‐ or p ‐quinone methide (QM) intermediates. These intermediates undergo an unusual oxy‐anion accelerated [1.5]‐QM shift followed by intramolecular Michael addition and subsequent nucleophilic epoxidation. The [1.5]‐shift is computed to be exothermic by over 28 kcal/mol and has a barrier of 3.2 kcal/mol.